Energy Expenditure and Dietary Intake of Female Collegiate Tennis and Soccer Players during a Competitive Season (Kinesiology, 2019)
This study examined energy expenditure, dietary behavior, and energy balance of female tennis and soccer student-athletes during a competitive season. A sample of 18 (Mage = 19.86±1.35) Division I female collegiate student-athletes (5 tennis and 13 soccer players) were followed for four days. Physical activity was assessed with accelerometers and dietary behavior with daily food logs. Daily energy expenditure for the game/match, practice, and rest days was 2,848±304kcals, 2,622±248kcals, and 1,833±959kcals, respectively, with a statistically significant main effect (F(2,16) = 82.291, p < .001, η2= .91). Daily dietary intake ranged from 1,833±959 to 1849±371kcals, with no significant interaction between different days.  There were no sport specific differences in energy expenditure or dietary behaviors. Athletes consumed 4.30±2.07 g/kg carbohydrates, 1.57±.98 g/kg protein, and 1.27±.80 g/kg fats daily. There was a significant main effect in dietary intake (F(2,16) = 7.311, p = .006, η2= .48), with  a difference between game/match and recovery days (t(17) = 3.83, p = .001, d = 1.19). This study showed a negative energy balance among female student-athletes. The findings indicate that the lack of carbohydrate intake during game/match days contributed to this negative energy deficit.